Transformative Mosque Model in Social Entrepreneurship: From Trash Donation to FreeVegetables and Youth Participation - Choiriyah, Arifatul; Maulana Rohimat, Asep; Islahuddin, Islahuddin (Fakultas Ekonomi dan Bisnis Islam, 2024)
The issue of cleanliness around mosques, often filled with trash and waste, poses challenges for the youth, along with the lack of economic innovation from mosque management, remains a significant obstacle in many communities. However, the management of Masjid al-Muttaqiin in Colomadu, Karanganyar, with the support of a youth organization called RISTAQ (Remaja Islam Masjid Al-Muttaqin), has developed two innovative social entrepreneurship programs: Waste Donation and the Affordable Vegetable Market. Through this initiative, the mosque not only serves as a place of worship but also plays an active role in maintaining environmental cleanliness. Another innovative program is the “Amal Bahagia” affordable vegetable market, held every Sunday morning alongside religious study sessions. This research employs a descriptive qualitative method, with data collected through field observations and in-depth interviews with informants. Findings indicate that the Waste Donation program and the affordable vegetable market not only address environmental and economic issues but also empower the mosque's youth as active agents of change.